Refractory cardiac arrest: where extracorporeal cardiopulmonary resuscitation fits. Issue 6 (December 2020) - Bartos, Jason A.; Yannopoulos, Demetris
Abstract : Purpose of review: Extracorporeal cardiopulmonary resuscitation (ECPR) is a powerful technique increasingly used to care for patients with refractory cardiac arrest. This review will detail where ECPR fits in the current care of cardiac arrest patients, including the key aspects of ECPR deployment and patient selection shown to maximize its benefit. Recent findings: ECPR has been shown to improve neurologically favourable survival in patients with refractory cardiac arrest in numerous nonrandomized cohort studies. The haemodynamic, oxygenation and ventilation support provided by ECPR eliminates the need for return of spontaneous circulation (ROSC) and prevents ongoing injury from shock or rearrest. However, ECPR is one component of an entire system of resuscitation care necessary for positive outcomes. The intense resources needed require that patient eligibility criteria are well delineated to direct ECPR to patients likely to benefit. The other components of the system, including emergency medical services, cannulation teams and postarrest care teams, also require substantial training and dedication. Summary: ECPR is a system of resuscitation care that must be optimized at every level to successfully treat patients with refractory cardiac arrest.